Work Readiness of BSBA OJT Students in a Private Catholic Institution: A Student-Supervisor Comparative-Correlational Assessment (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Work readiness is essential in helping business students transition from academic learning to employment because it reflects their ability to apply knowledge, technical competencies, communication skills, professionalism, interpersonal abilities, self-management, and ethical responsibility in actual workplace settings. This study aimed to assess the work readiness of Bachelor of Science in Business Administration On-the-Job Training students based on their self-assessments and the evaluations of Host Training Establishment supervisors as a basis for enhancing the On-the-Job Training manual. A quantitative descriptive-comparative design was employed among 94 Bachelor of Science in Business Administration On-the-Job Training students selected through total enumeration and 50 Host Training Establishment supervisors selected through purposive sampling. Data were gathered using validated questionnaires with content validity indices of 0.93 and 0.94 and a Cronbach’s alpha coefficient of 0.979. For descriptive statistics, frequency, percentage, mean, and standard deviation were used. For inferential statistics, the t-test and analysis of variance were employed to determine significant differences, while Pearson’s correlation coefficient was used to examine the relationship between the variables. Findings revealed that the students demonstrated a generally very high level of work readiness across the seven dimensions. Most differences based on the profiles of the students and supervisors were not statistically significant. However, knowledge competency varied significantly across industry categories, while work attitude and professionalism differed significantly according to the position of the Host Training Establishment Supervisor. The assessments of the students and supervisors showed a moderate positive but statistically non-significant relationship. The study concluded that Bachelor of Science in Business Administration On-the-Job Training students were generally prepared for workplace demands. However, student self-assessments and supervisor evaluations represented distinct yet complementary perspectives that should both be considered in evaluating work readiness. The institution should enhance the On-the-Job Training manual by providing clearer competency standards, structured orientation, industry-aligned tasks, regular monitoring, consistent evaluation tools, and scheduled feedback sessions involving students, On-the-Job Training coordinators, and Host Training Establishment supervisors. Based on the findings, the Integrated Work Readiness Enhancement and Industry Bridging Program was proposed.